Development and sensory testing of cranberry chutney and biscotti - Herl, Bethany; Alexander, Hannah; Mills, MaKenna; Savage, Sierra; Getty, Kelly J.K. (My University, 2017)
The purpose of this project was to develop a new food product for healthy strivers that included whole cranberries for the 2016-2017 Ocean Spray Cranberry Competition. The product was customized for people on-the-go. The specific objective was to evaluate sensory aspects of the cranberry chutney and biscotti. A secondary objective was to discuss formulation and processing issues that occurred during the development phase of the chutney and biscotti. The initial concept was to develop a cranberry salsa and to compliment it with a gluten-free biscotti stick. Due to the lack of tomatoes, the product was renamed as a cranberry chutney with a spicy profile coming from peppers. The chutney was too spicy in the original formulation due to the addition of multiple peppers. For the biscotti stick, the Maillard browning reaction was not optimal. To evaluate the sensory properties and to obtain consumer feedback on the chutney and biscotti, a focus group was conducted. The panelists were asked to rate a prototype of the chutney and biscotti on a scale of 1 to 10 with 1=extremely dislike and 10=extremely like. The averages of these scores are shown in Figure 1. For the final formulation, only Anaheim peppers were added to provide a unique “sweet and heat” profile (Table 1). To develop a stronger Maillard browning reaction, a raw egg mixture was brushed on top of the biscotti sticks prior to baking. Figure 1 shows the average ratings of the prototype(n=). A panel of college-age individuals reviewed the final products and 70% of the participants stated that they would buy this product as a snack. The cranberry chutney by itself was perceived to be a marketable product by the panelists. Therefore, the next steps will be to pursue this as a potential new product to be made by Food Science Club and sold at the Call Hall Dairy Bar.
Keywords: Spring 2017